A multi-faceted approach to the physiologically unstable patient. Issue 5 (29th July 2010) - Robb, Gillian; Seddon, Mary
Abstract : Background: Patients on general hospital wards who deteriorate clinically are often not recognised as needing an escalation in care, and effective interventions are delayed. This study reviews a multifaceted approach to the identification and management of these patients in a large metropolitan hospital in Auckland, New Zealand. Strategies for change: Four interventions were combined into the Physiologically Unstable Patient (PUP) programme. These were: (1) redesign of the vital sign observation chart; (2) introduction of an early warning scoring system; (3) deployment of a nurse-led rapid response team; and (4) a comprehensive ward-based education programme. Key measures for improvement: Completeness and accuracy of routine observations; actions taken in accordance with the algorithm; impact on medical emergency team callouts, cardiac arrest calls and unplanned intensive care unit admissions. Effects of change: The PUP programme was implemented in 16 wards over 15 months. Vital sign recording improved, and the PUP score became a recognised metric for prioritising patients for review. Consistent with others' experience, there was a reluctance to call for help. Raised PUP scores prompted action around 30% of the time on average. Medical emergency team calls increased significantly from a median of 27.5 calls per month to 70.5. There was no significant change in unplanned transfers to intensive care unit or in cardiac arrest calls. Lessons learnt: A multifaceted programme to identify physiologically unstable patients on general wards can be introduced and can improve the recognition of such patients, but there are still barriers to ensuring that these patients receive the extra care that they require. These systemic failings need to be investigated and addressed for real change to occur.